Edukasi Mata Uang Baru Emisi 2022 dan Menghindari Mata Uang Palsu - Puspita Ayu, Baiq Dinda; Ika Putri Fitri Ajiani; Ana Rahmatyar; Widani Darma Isasih; Rizqa Inayati (Insan Kreasi Media, 2023)
The service program is one of the obligations of lecturers from the implementation of the tri dharma of higher education which must be carried out. Bumigora University service team has successfully carried out community service activities at RA ASH Shofa Wasalam. The results of this activity are to increase awareness of the importance of introducing the new 2022 currency by using 3d techniques to prevent the spread of counterfeit currency, the team provides outreach through playing and singing, delivering material through stories related to the introduction of the 2022 new currency issuance and 3d techniques to find out the authenticity of currency explained the benefits of 3d techniques for children in the future, and quizzes. Teaching the importance of the benefits of the 3d technique to distinguish fake and genuine currency can shape children's character, children will be more responsible for the money they have, introduce the value of money later, children will be able to distinguish between real and fake. An easy way to teach children to take care of themselves and not be quickly swayed by fraud that is rife.